Growth Regulator Test on Upland Cotton at the Marana Agricultural Center, 1988 - Briggs, R. E. (College of Agriculture, University of Arizona (Tucson, AZ), 1989)
A field study was conducted at the Marana Agricultural Center to evaluate the effectiveness of growth regulators on Deltapine 90 cotton. The Pix treatment yielded significantly higher than the check and any of the other treatments.